Renoprotective Effect of Lactoferrin against Chromium-Induced Acute Kidney Injury in Rats: Involvement of IL-18 and IGF-1 Inhibition - Hegazy, Rehab (PLoS One, 2016)
Hexavalent chromium (CrVI) is a heavy metal widely used in more than 50 industries. Nephrotoxicity is a major adverse effect of chromium poisoning. The present study investigated the potential renoprotective effect of lactoferrin (Lf) against potassium dichromate (PDC)-induced acute kidney injury (AKI) in rats. Beside, because previous studies suggest that interlukin-18 (IL-18) and insulin-like growth factor-1 (IGF-1) play important roles in promoting kidney damage, the present work aimed to evaluate the involvement of these two cytokines in PDC model of AKI and in the potential renoprotective effect of lactoferrin. Adult male albino Wistar rats were pretreated with Lf (200mg/kg/day, p.o.) or (300mg/kg/day, p.o.); the doses that are usually used in the experiment studies, for 14 days followed by a single dose of PDC (15mg/kg, s.c.). PDC caused significant increase in serum urea, creatinine, and total protein levels. This was accompanied with decreased renal glutathione content, and increased renal malondialdehyde, IL-18, IL-4, nuclear factor kappa B (NFκB), IGF-1, and the phosphorylated form of forkhead box protein O1 (FoxO1) levels. Moreover, normal expression IFN-γ mRNA and enhanced expression of TNF-α mRNA was demonstrated in renal tissues. Histopathological investigations provoked deleterious changes in the renal tissues. Tubular epithelial hyperplasia and apoptosis were demonstrated immunohistochemically by positive proliferating cell nuclear antigen (PCNA), Bax, and Caspase-3 expression, respectively. Pretreatment of rats with Lf in both doses significantly corrected all previously mentioned PDC-induced changes with no significant difference between both doses. In conclusion, the findings of the present study demonstrated the involvement of oxidative stress, inflammatory reactions, tubular hyperplasia and apoptosis in PDC-induced AKI. It suggested a role of IL-18 through stimulation of IL-4-induced inflammatory pathway, and IGF-1 through triggering FoxO1-induced cell proliferation. Moreover, the study revealed that Lf protected the kidney against Cr-induced AKI in rats and significantly showed antioxidant, anti-inflammatory, and anti-proliferative properties with down-regulation of IL-18 and IGF-1.